PROSPEK PENGEMBANGAN TANAMAN TOMAT (Solanum lycopersicum L) DI DESA MURUNG A KECAMATAN BATU BENAWA KABUPATEN HULU SUNGAI TENGAH PROVINSI KALIMANTAN SELATAN - Ahmad Baparki (Fakultas Pertanian UVAYA Banjarmasin, 2025)
The prospect of developing Tomato plants (Solanum lycopersicum L.) in Murung A Village, Batu Benawa District, Hulu Sungai Tengah Regency, South Kalimantan Province”. Total production is 52,892 kg with an average of 4,408 kg/farmer. Income is the multiplication of total production by the current price, with an average of Rp 28,649,833,-/farmer. The average income obtained by farmers in one harvest season is Rp 18,676,545,-/farmer and the average profit obtained by tomato farmers is Rp 15,530,820.